Kelayakan bahan ajar interaktif berbasis problem-based learning pembelajaran PPKn pada Siswa Kelas V SD - Lina Risti (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this study was to determine the feasibility of interactive teaching materials based on problem-based learning in Civics learning for fifth grade elementary school students in Mayong District, Jepara Regency. Sources of data with interviews, questionnaires, and documentation. Quantitative and qualitative research methods. Data were analyzed by accumulating the number of scores. Analysis of the data from the expert validation test results, student and teacher responses were obtained using the percentage calculation of the score obtained with the maximum score and description. The results of the research are the feasibility of teaching materials which are validated by material experts, teaching materials experts and practitioners each 90.00; 89.5, and 89 â€œvery feasibleâ€ criteria. The results of the responses from students were 87.53% and the average response of the three teachers was 88.89% with the "very feasible" category. Problem-based learning-based interactive teaching materials are proven to be suitable for use as a teaching chart for Civics learning for fifth graders in elementary schools in Mayong District, Jepara Regency.